Equus capensis (Mammalia, Perissodactyla) from Elandsfontein - Eisenmann, Vera (Bernard Price Institute for Palaeontological Research, 2000)
The skull and limb bones collected at Elandsfontein, Cape indicate that E. capensis was different from a Grevy's zebra. The body proportions were similar to those of an extant draft horse (E. caballus) and the skull resembled those of true Cape quaggas and a fossil Algerian plains zebra, E. mauritanicus.
Keywords: Pleistocene; Elandsfontein; equus capensis; zebras